PHYSIOTHERAPY MANAGEMENT FOR POST RECONSTRUCTION POSTERIOR CRUCIATE LIGAMENT ACUTE PHASE: A CASE STUDY - Monitari, Triska; Supriyadi, Arin; Mardianto, Halim (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Rupture is a tear of tissue caused by trauma. Posterior Cruciate Ligament (PCL) ruptures can be caused by direct or indirect contact with the knee. A grade 3 PCL injury requires surgery. Rehabilitation in PCL injuries focuses on quadriceps muscle augmentation to counteract the force of the hamstrings muscles and the gravity that move the tibia towards the posterior. Case Presentation: A football athlete suffered a knee injury while playing football. From mri examination found the diagnosis of rupture PCL sinistra grade 3, then undergo reconstruction surgery PCL sinistra. The results of the examination there are several problems in patients, such as oedem, atrophy, spasm, pain (press &motion), and limited motion. Management and outcome:interventions given in the form of exercise therapy as much as 3 times. Pain measured by Numeric Rating Scale (NRS), oedem (metline), range of motion (gonio meter). Discussion: Based on the interventions provided found results that exercise has benefits in patients post acute phase PCL reconstruction that has the goal of maximum protection on grafting, maintaining patellar mobility, maintaining quadriceps muscle tone, maintaining full passive extensions, controlling pain and oedem, early mobilization in knee joints Conclusion:Intervention in the form of exercise therapy can relieve pain, reduce oedem and improve ROM in patients post acute phase PCL reconstruction.